Information Technologies in Genetics - N. A. Balashenko (Цифровая трансформация)
The article describes and groups on directions the experience of information technologies in genetics. Currently a huge amount of data received in genetics as part of large-scale projects, and it requires processing. The only way to handle these data is use of information technology.